Edukasi Diabetes untuk Remaja Dipanti Aisyiyah : Meningkatkan Kesadaran dan Pencegahan - Ribka S Panjaitan; Yurita Mailintina; Ludovikus Ludovikus; Fendy Yesayas; Indri Meilawati; Muhammad Rizqi Ar Rasyid; Angelica Abel Valerina; Fitriana Indi Rahayu (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Diabetes mellitus is one of the main causes of morbidity and death in developing countries. Diabetes mellitus in adolescents is increasing from year to year, causing serious complications such as heart disease, kidney disease and other metabolic disorders. It is very important to prevent diabetes mellitus through education, because providing the public with understanding about healthy lifestyles can reduce the risk of developing diabetes. This community service aims to increase knowledge and understanding about Diabetes Mellitus as well as education about routine health checks at Panti Aisyiyah Jakarta. This intervention was carried out by measuring changes in knowledge through a pre-test and post-test used to evaluate changes in respondents' knowledge. The evaluation results showed a significant increase in participants' knowledge about diabetes mellitus and the importance of routine health checks. Pre-test and post-test are used to evaluate respondents' knowledge, by calculating the mean and variation values ​​for each condition. The N-Gain Score is used to evaluate the increase in adolescent knowledge regarding diabetes mellitus education and routine health check education. The success of this intervention is proven by the N-Gain Score of 0.70 which is in the medium category and an effectiveness value of 69.83, meaning that the method used is quite effective. These results show that the health education provided can increase teenagers' awareness and understanding of diabetes mellitus, so it is hoped that it can help in preventing and controlling this disease among teenagers.